MUKJIZAT AL-QURAN DALAM BERBAGAI ASPEKNYA - Abdurahman, Abdurahman (LPPI Universitas Al-Qolam Malang, 2017)
Mu'jizah or miracle is not only owned by Muhammad, but also the prophets and messengers of Allah before him, to prove the truth of the prophetic and apostolic respectively to the opponents. With the miracle, God reminds us that the apostles are messengers who had the support and help of heaven. Guidance and direction given in a community should be related to their knowledge because God will not direct a people on things they do not know. Therein lies the miracle that was given to the Prophet.al-Qur'an was delivered by God to people not only to be a source of teaching, but also to be a proof of the prophethood of Muhammad. The truth in question is to challenge those who reject proselytizing, preaching. Evidence of the truth in the study of al-Qur`an is called mu'jizah or the miracle of al-Qur`an. The concept of the miracle of the Qur'an, which was introduced by scholars revolves around three aspects, namely the beauty and precision of the wording, known as al-i'jÄz al-bayan, news-reporting supernatural aspect termed al-i'jÄz al-akhbar, and scientific aspects of the signal, known as al-i'jÄz al-'ilm. Keywords: Mu'jizah, Al-Qur'an, Aspects